Improving the Capabilities of Village Officials in the Management of Village-Owned Enterprises and Understanding Village Data - Rivai ahmad; Badruzzaman; Afrida Hanum; Muklis; Nazaruddin; Siti Rahmatina; Rizkal; Riantofani; Fuady (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: Village-Owned Enterprises (VOEs), mandated by Law No. 6 of 2014, are crucial for driving village economies and improving community welfare. However, many village officials face challenges understanding sound business governance and the significance of village data for effective development planning. Method: The activity included lectures on VOE and village data, interactive discussions between facilitators and participants, and practical simulations for managing VOEs and compiling village data. Conducted smoothly in Naga Umbang Village, the program involved preparation, implementation, ongoing guidance, and evaluation to ensure success and sustainability. Practical Applications: Professional management of businesses through transparent governance—such as financial record-keeping, clear role division, and operational rules—and integrating village data in planning based on asset inventories, population, and economic potential. Conclusion: This activity enhanced the knowledge and skills of village officials and VOE administrators, fostering more professional VOE management and better utilization of village data for sustainable village development.